On a Family of Multivariate Modified Humbert Polynomials - Rabia Aktaş; Esra Erkuş-Duman (The Scientific World Journal)
This paper attempts to present a multivariable extension of generalized Humbert polynomials. The results obtained here include various families of multilinear and multilateral generating functions, miscellaneous properties, and also some special cases for these multivariable polynomials.